Brewing optimization for functional properties and visual appearance of Dampit Robusta coffee leaves tea - Kiki Fibrianto; Sudarminto Setyo Yuwono; Laila Yum Wahibah (Advances in Food Science, Sustainable Agriculture and Agroindustrial Engineering (AFSSAAE), 2021)
Coffee leaf tea is made by drying coffee leaves in an oven at 70oC for 4 hours. The quality of coffee leaves tea does not only depend on the process of making tea but also the way the tea is brewed. There were 2 types of brewing techniques investigated in this study, namely infusion and decoction. Response Surface Methodology (RSM) was conducted to optimize the brewing time and temperature for obtaining highly functional coffee leaves tea with optimum total phenolic content (TPC) and antioxidant activity. The Rate-All-That-Apply (RATA) sensory technique was then applied to determine the sensory characteristics of coffee leaf tea. It was observed that optimum tea quality brewed by hot infusion technique was obtained at 80.03oC for 10.4 minutes while that of decoction technique was obtained at 95.38oC for 5.7 minutes. The coffee leaves tea brewed by decoction technique have higher total phenolic content, tannin and antioxidant activity than that of infusion technique (p-value<0.05). Even though the functional properties of coffee leaves tea such as total phenolic content and antioxidant activity, tended to be lower than that of commercial black tea, the coffee leaves tea is still more superior than that of tea leaves that prepared as the process of coffee leaves tea. The coffee leaves tea that brewed by both decoction and infusion techniques were well accepted by consumer panel.